DEVELOPING READING MATERIALS THROUGH AUTHENTICITY-CENTERED APPROACH (ACA) FOR GRADE X STUDENTS OF COMPUTER NETWORK ENGINEERING IN SMK YAPIM 1 MEDAN - Tania La Rose; yeni erlita; Maya Oktora (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
The objectives of this study wasto develop the reading materials in descriptive text for grade ten students of computer network engineering in SMK YAPIM 1 Medan. This study was conducted a Research and Development (R&D). The subjects of the study were the students of grade ten students of computer network engineering in SMK YAPIM 1 Medan consisting of 29 students. The research procedures, were adapted from Jolly and Bolitho’s model in Tomlinson (1998) with some modifications, consisting of conducting the need analysis, writing the course grid, developing draft, getting expert judgment and evaluating the draft, also revising the draft of the materials.The instruments to collect the data were need analysis questionnaire and expert judgment questionnaire. The data from the need analysis were analyzed quantitatively using frequency and precentage, then the results were used to develop the course grid. The data from the expert judgment were analyzed quantitatively through descriptive statistics while the suggestions were used to revise the first draft of the materials.The product of this study is a set of writing materials of recount text entitled “Well-performing and Affordable Netbooks” for grade ten students of computer network engineering in SMK YAPIM 1 Medan. It  consists of introduction, main lesson and reinforcement. Keywords:Descriptive Text, Reading Materials, R&D Method